Eco-Score Tracker - Eco-score computation system for OBD-II equipped cars running on Android-based Raspberry Pi 4 - DOBNER, NÁTÁN; HAMDO, EBRAHIM (My University, 2024)
Vehicle electronic systems today have the computation power of small computers, but this technology has not always been available, as in the case of older cars. The aim of this project is to make modern technologies available for older vehicles by developing an Android application that utilizes the OBD-II protocol, and run it on a Raspberry Pi with Android Automotive OS to mimic a modern car UI. The application reads and saves vehicle data on the user’s trips and provides a score based on the driving style and statistics of each trip. The application is developed in Android Studio and is tested throughout the development phase in real cars, assessing whether the concept is technically feasible. The results show that the key limitation is the OBD-II protocol itself, because, although the protocol is available in most cars, the supported commands vary drastically between car manufacturers. Regardless, the data acquisition itself from the OBD-II works well in the application, providing a score which allows the user to optimize their driving style in order to reduce their environmental impact.
Keywords: Android; OBD-II; Raspberry Pi; On-Board Diagnostics; vehicle data